Pengaruh Stres Belajar dan Nilai Akademik Terhadap Kesehatan Mental Remaja SMAN 5 Tangerang Selatan dengan Analisis Skala Linear: Penelitian - Anastasia Marshanda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Academic-related stress is a significant issue for students due to various factors that influence learning styles and academic outcomes. One key factor is the drive to achieve high grades. Students face a heavy burden of completing assignments or projects assigned by teachers to standards that meet the Minimum Completion Criteria (KKM). Stress, particularly in academic settings, can alter student behavior, including mental health issues like anxiety and depression, physical changes like headaches, and various aspects of pressure related to achievement, motivation, time, and ongoing psychological impacts. The research results show a positive and significant relationship (Significant) of 0.000 < 0.05, indicating that the hypothesis is accepted that there is an influence between the two variables, learning motivation and academic stress, on mental health. The correlation between the three variables is 0.340, indicating a weak, positive relationship with mental health. The R-squared value is 0.115, or 11.5%. This means that 11.5% of learning motivation and academic stress contribute to adolescent mental health. The research is expected to increase insight, the researcher also suggests that future researchers add many theories to this research.